Assessment of the safety and probiotic properties of Roseburia intestinalis: A potential “Next Generation Probiotic” - Zhang, Chao; Ma, Kejia; Nie, Kai; Deng, Minzi; Luo, Weiwei; Wu, Xing; Huang, Yujun; Wang, Xiaoyan (Frontiers in Microbiology, 2022)
Roseburia intestinalis is an anaerobic bacterium that produces butyric acid and belongs to the phylum Firmicutes. There is increasing evidence that this bacterium has positive effects on several diseases, including inflammatory bowel disease, atherosclerosis, alcoholic fatty liver, colorectal cancer, and metabolic syndrome, making it a potential "Next Generation Probiotic". We investigated the genomic characteristics, probiotic properties, cytotoxicity, oral toxicity, colonization characteristics of the bacterium, and its effect on the gut microbiota. The genome contains few genes encoding virulence factors, three clustered regularly interspaced short palindromic repeat (CRISPR) sequences, two Cas genes, no toxic biogenic amine synthesis genes, and several essential amino acid and vitamin synthesis genes. Seven prophages and 41 genomic islands were predicted. In addition to a bacteriocin (Zoocin A), the bacterium encodes four metabolic gene clusters that synthesize short-chain fatty acids and 222 carbohydrate-active enzyme modules. This bacterium is sensitive to antibiotics specified by the European Food Safety Authority, does not exhibit hemolytic or gelatinase activity, and exhibits some acid resistance. R. intestinalis adheres to intestinal epithelial cells and inhibits the invasion of certain pathogens. In vitro experiments showed that the bacterium was not cytotoxic. R. intestinalis did not affect the diversity or abundance of the gut flora. Using the fluorescent labelling method, we discovered that R. intestinalis colonizes the cecum and mucus of the colon. An oral toxicity study did not reveal any obvious adverse effects. The lethal dose (LD)50 of R. intestinalis exceeded 1.9 × 109 colony forming units (CFU)/kg, whereas the no observed adverse effect level (NOAEL) derived from this study was 1.32 × 109 CFU/kg/day for 28 days. The current research shows that, R. intestinalis is a suitable next-generation probiotic considering its probiotic properties and safety.